Mental health problems of front-line medical staff in the early stage of public health emergencies - Wang, Dong-Bao; Jiang, Jin-Bo; Zhang, Hai-Jun; Wu, Di; Zhang, Ya-Hong; Cui, Long-Biao; Zhang, Jian; Wang, Xiao-Hui (Frontiers in Psychiatry, 2024)
In the face of the unprecedented public health crisis caused by the novel coronavirus pneumonia epidemic, front-line health workers are under enormous mental pressure. This paper aims to explore the mental health challenges faced by front-line health workers in the early stages of a public health emergency, such as stress, anxiety, and depression. At the same time, the factors that increase their mental stress are analyzed, and practical measures are put forward to prevent and manage mental health problems, aiming at improving the quality of medical treatment during public health emergencies. This paper has some reference value for people engaged in mental health prevention.